2016
DOI: 10.1080/21505594.2016.1257457
|View full text |Cite
|
Sign up to set email alerts
|

New facets of antifungal therapy

Abstract: Invasive fungal infections remain a major cause of morbidity and mortality in immunocompromised patients, and such infections are a substantial burden to healthcare systems around the world. However, the clinically available armamentarium for invasive fungal diseases is limited to 3 main classes (i.e., polyenes, triazoles, and echinocandins), and each has defined limitations related to spectrum of activity, development of resistance, and toxicity. Further, current antifungal therapies are hampered by limited c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 124 publications
1
98
0
3
Order By: Relevance
“…Several authors have demonstrated the beneficial interactions between different antifungal agents 11,24‐26 . Double and triple associations using clioquinol showed synergistic effect in the present study, and this complex interaction can be explained by the fact that each of the three drugs has simultaneous effect on different targets.…”
Section: Discussionsupporting
confidence: 64%
“…Several authors have demonstrated the beneficial interactions between different antifungal agents 11,24‐26 . Double and triple associations using clioquinol showed synergistic effect in the present study, and this complex interaction can be explained by the fact that each of the three drugs has simultaneous effect on different targets.…”
Section: Discussionsupporting
confidence: 64%
“…1·2 billion individuals worldwide with at least 1·5 million deaths each year (Campoy and Adrio ; Chang et al . ). Furthermore, the widespread use of antifungal drugs are bringing serious consequences for antifungal therapy, due to the emergence of resistant strains and therefore leading to treatment failures (Pfaller ; Tobudic et al .…”
Section: Introductionmentioning
confidence: 97%
“…Combination antifungal therapy is of increasing interest as a means to modulate antifungal resistance and/or improve antifungal efficacy (24). To assess the interactions between currently used antifungal drugs and MEF-derivatives, we performed checkerboard microdilution assays and analyzed data using the fractional inhibitory concentration index (FICI).…”
Section: Resultsmentioning
confidence: 99%